ANALISIS PENGARUH CHALLENGE STRESSORS TERHADAP KOMITMEN AFEKTIF DAN KINERJA DOSEN DENGAN KETERIKATAN KERJA SEBAGAI PEMEDIASI PADA DOSEN UNIVERSITAS SYIAH KUALA - Rika Zulfia, Amri (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
ABSTRACTThis study aims to determine the effect of challenge stressors on affective commitment and lecturer performance with work engagement as a mediator. Empirical study was conducted on lecturers of Syiah Kuala University using questionnaires as research instruments, in which the sample in this study is 121 people who are lecturers who have structural positions. Non Probability Sampling is used as sampling technique with Purposive Sampling method. The Hierarchical Linear Modeling (HLM) method was used as a data analysis method using the IBM SPSS 20 software. The results of this study indicate that the challenge stressors have a positive and significant effect on the affective commitment of lecturer performance and work attachment, and the work attachment has positive and significant influence on affective commitment and The performance of lecturers in addition to the results obtained that the attachment of work mediate the positive influence of challenge stressors on affective commitment and lecturer performance. Keywords: Challenge Stressors, Organizational affective Job performance, Collenge lecturer, dan Work Engagement